The opinions of students, professors and practice teachers on the teaching practice course - Esra Töre (International Journal of Evaluation and Research in Education (IJERE), 2020)
The goal of this study was the evaluation of the teaching practice course in the Psychological Counseling and Guidance (PCG) department by students, professors and practice teachers. It was a pneumology study designed with qualitative research method. The study group consists of seven students, five professors and five practice teachers from 3 different schools and 3 different universities in İstanbul. Study data were analyzed with content analysis. It was found that the communication and collaboration between the professors and practice teachers of the teaching practice course were low, and the applications within the scope of the course were inadequate. Additionally, the study has revealed that it is necessary to inform the practice teachers about the previous courses and internships the students have taken, to ensure the attendance of students to full-day practice courses on different days and that a detailed teaching practice course guide is prepared. This study is thought to benefit the literature in the sense that it shows how PCG teaching practice course differs from other teaching practice courses, in addition to suggestions to the decision makers and practitioners for improving the course.